IDEOLOGY AND POWER DYNAMICS IN PRESIDENT TRUMP'S FAREWELL ADDRESS: A CRITICAL DISCOURSE ANALYSIS (Malaysian Journal of Applied Linguistics (MJoAL), 2023)
This analysis focuses on President Trump's Farewell Address, utilizing Critical Discourse Analysis (CDA) and Fairclough's Three-Dimensional Model. Its objective is to examine the rhetorical strategies employed in the address, such as repetition, hyperbolic language, antithesis, and narrative structure. The analysis also takes into account sociocultural context factors along with power dynamics and ideological positioning evident in the address. The findings highlighted how language choices impact persuasion within political discourse by constructing a cohesive message that reinforces American values while inspiring hope for future endeavours. However, it is important to note that this analysis only focuses on a single case study without comparing President Trump's discourse with other political figures' speeches or statements. To gain a more comprehensive understanding of his communication style and strategies, future research could expand its scope by incorporating a wider range of speeches from different contexts considering sociocultural factors with multiple perspectives.